Re-evaluation of the etiology and clinical and radiological features of community-acquired lobar pneumonia in adults. Issue 6 (June 2018) - Ishiguro, Takashi; Yoshii, Yutaka; Kanauchi, Tetsu; Hoshi, Toshiko; Takaku, Yotaro; Kagiyama, Naho; Kurashima, Kazuyoshi; Takayanagi, Noboru
Abstract: Objective: The aims of this study were to elucidate the frequency and etiology of community-acquired lobar pneumonia (CALP) and the clinical and radiological differences between CALP and tuberculous lobar pneumonia (TLP). Patients and Methods: We retrospectively reviewed medical records of patients with community-acquired pneumonia (CAP) (n = 1032) and tuberculosis (n = 1101) admitted to our hospital. Results: Sixty-nine (6.7%) patients with CAP and 23 (2.1%) with pulmonary tuberculosis developed CALP. Legionella species were the most common pathogen (27 patients, 39.1%), followed by Streptococcus pneumoniae (19 patients, 27.5%) and Mycoplasma pneumoniae (18 patients, 26.1%). Symptom duration was longer in the patients with TLP than in those with CALP. On chest radiographs, cavitation in the area of lobar pneumonia and nodular shadows were radiological findings predictive of TLP. High-resolution computed tomography showed cavitation in the area of lobar pneumonia, well-defined centrilobular nodules, and tree-in-bud sign to be the radiological findings predictive of TLP by multivariate logistic regression models. Conclusion: Common causes of CALP are Legionella species, S. pneumoniae, and M. pneumoniae . TLP should be considered in patients with lobar pneumonia, particularly in patients with long symptom duration, cavitation, and nodular shadows on chest radiographs, and cavitation, well-defined centrilobular nodules, and tree-in-bud sign on CT.